Knowledge, Prevalence, and Perception of the Use of Skin-Lightening Products among Female Undergraduates in the University of Calabar - Eyo, Precious-Gift Effiom; Peter Alexander; Esther E. Eyo; Fidel Takim Otu; Leonard O. Umunnakwe (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: To assess the knowledge, prevalence, and perception of skin-lightening products among female undergraduates in the University of Calabar. Methods: A descriptive cross-sectional study was conducted using an interviewer-administered semi-structured questionnaire. Data from 402 female undergraduates were analyzed using SPSS version 22. Results: The study found that 69.8% of respondents were familiar with skin-lightening products, and 53.7% had used them. The main reasons for use were achieving a lighter skin tone (90.5%) and social pressure (62.3%). Conclusion: Skin-lightening product use is prevalent among female undergraduates. Public awareness campaigns and stricter regulations are needed to address the health risks associated with these products. Skin-lightening products, commonly referred to as bleaching or whitening products, have gained significant popularity worldwide, particularly among women. In recent years, there has been growing concern about the widespread use of skin-lightening products and the potential health risks, social implications, and ethical considerations associated with them. Research reveals that these products often contain harmful ingredients such as hydroquinone, mercury, and corticosteroids, which can have detrimental effects on the skin, including skin thinning, discoloration, and increased vulnerability to infections. This study sought to assess the knowledge, prevalence, and perception of the use of skin-lightening products among female undergraduates in the University of Calabar. A descriptive cross-sectional study design was employed for the study using interviewer-administered semi-structured questionnaires. Quantitative data was collected from 402 female undergraduates enrolled in the University of Calabar which was analysed using SPSS version 22. Results revealed that most of the respondents (34.1%) were between the ages of 21 to 23 years, about (34.1%) were between the ages of 16 to 20 years and those between 27 years and above made up the least number of children. The study also showed that less than three-quarter (69.8%) indicated that they have a good understanding of what skin-lightening products are. Nearly three-quarter (72.7%) indicated that they understand the potential risks and side effects associated with skin-lightening products when used. Also, results showed that more than half (53.7%) of the respondents indicated that they have used lightening products. This study sheds light on the nuanced landscape surrounding skin-lightening product knowledge, prevalence, and perceptions among the surveyed population. However, strengthening regulations around the marketing and sale of skin-lightening product.